2022
DOI: 10.3390/genes13101777
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the MADS-Box Gene Family in Akebia trifoliata and Their Evolutionary Events in Angiosperms

Abstract: As the largest clade of modern plants, flower plants have evolved a wide variety of flowers and fruits. MADS-box genes play key roles in regulating plant morphogenesis, while basal eudicots have an evolutionarily important position of acting as an evolutionary bridge between basal angiosperms and core eudicots. Akebia trifoliata is an important member of the basal eudicot group. To study the early evolution of angiosperms, we identified and characterized the MADS-Box gene family on the whole-genome level of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Both the selection style and duplication type of members are the two most important factors when we investigate the evolutionary history of a given gene family. Here, we only found one homogenous gene pair (AktPG15 and AktPG17) with a Ka/Ks value (1.122) larger than 1 among a total of 467 homologous gene pairs, while all the others were less than 1 or even 0.5 (Supplementary Table S1), which suggested that AktPGs as well as AktNBSs [43], AktMADS-boxs [44], AktWRKYs [45], AktNACs [46], AktSODs [47], and AktDofs [48] experienced strong purifying selection in the evolutionary process.…”
Section: Putative Evolutionary Events Experienced By Aktpgsmentioning
confidence: 85%
“…Both the selection style and duplication type of members are the two most important factors when we investigate the evolutionary history of a given gene family. Here, we only found one homogenous gene pair (AktPG15 and AktPG17) with a Ka/Ks value (1.122) larger than 1 among a total of 467 homologous gene pairs, while all the others were less than 1 or even 0.5 (Supplementary Table S1), which suggested that AktPGs as well as AktNBSs [43], AktMADS-boxs [44], AktWRKYs [45], AktNACs [46], AktSODs [47], and AktDofs [48] experienced strong purifying selection in the evolutionary process.…”
Section: Putative Evolutionary Events Experienced By Aktpgsmentioning
confidence: 85%
“…PL cleaves the α-1,4-glycosidic bond of polygalacturonic acid by catalyzing the β-elimination reaction, degrading the de-esterified pectin. , In strawberries, silencing the PL gene could significantly increase fruit firmness and prolong the fruit shelf life. , In tomatoes, silencing the PL expression was shown to increase the skin break strength and firmness of the transgenic lines. , Moreover, researchers concluded that PL is a major contributor affecting the fruit texture, and its influence on the fruit texture is obviously greater than that of other genes involved in the cell wall metabolism . Recently, the expression levels of the PL gene and protein in Akebia trifoliata (commonly called August melon in China) were significantly higher in cracked fruits than in normal fruits, which indicate that PL may play an important role in regulating fruit cracking . In our previous study, VIT_05s0051g00590 (annotated as VvPL1 ) was also downregulated by preharvest calcium treatments that prevented berry cracking .…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Moreover, researchers concluded that PL is a major contributor affecting the fruit texture, and its influence on the fruit texture is obviously greater than that of other genes involved in the cell wall metabolism. 48 Recently, the expression levels of the PL gene and protein in Akebia trifoliata (commonly called August melon in China 49 ) were significantly higher in cracked fruits than in normal fruits, which indicate that PL may play an important role in regulating fruit cracking. 50 In our previous study, VIT_05s0051g00590 (annotated as VvPL1) was also downregulated by preharvest calcium treatments that prevented berry cracking.…”
Section: ■ Introductionmentioning
confidence: 99%